2018
DOI: 10.1002/app.46934
|View full text |Cite
|
Sign up to set email alerts
|

Facile access to carboxyl‐terminated polybutadiene and polyethylene fromcis‐polybutadiene rubber

Abstract: Carboxyl-terminated polybutadiene (CTPB) is a widely used telechelic liquid rubber, which is mainly prepared by anionic or free-radical polymerization of 1,3-butadiene. It is known that the microstructure of liquid polybutadiene rubber largely affects its processability and mechanical properties. However, it is hard to control its microstructure in the free radical or anionic polymerization. In this study, a series of CTPB with high cis-1,4 content has been prepared for the first time via the oxidolysis and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 49 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…To gain further insight into the effect of carboxylic acid incorporation on the properties of the functionalized polyethylene, we prepared polymers with different degrees of functionalization by varying the reaction time during the hydrocarboxylation. The residual double bonds in these samples were hydrogenated (Scheme ) using p -toluenesulfonyl hydrazide (TSH) in the presence of tri- n -propylamine (TPA) . ATR-FTIR (Figure a) unambiguously showed that the carboxylic acid peak (around 1710 cm –1 ) continued to increase linearly with the hydrocarboxylation reaction time (Figure b) allowing ready control of hydrocarboxylation levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To gain further insight into the effect of carboxylic acid incorporation on the properties of the functionalized polyethylene, we prepared polymers with different degrees of functionalization by varying the reaction time during the hydrocarboxylation. The residual double bonds in these samples were hydrogenated (Scheme ) using p -toluenesulfonyl hydrazide (TSH) in the presence of tri- n -propylamine (TPA) . ATR-FTIR (Figure a) unambiguously showed that the carboxylic acid peak (around 1710 cm –1 ) continued to increase linearly with the hydrocarboxylation reaction time (Figure b) allowing ready control of hydrocarboxylation levels.…”
Section: Resultsmentioning
confidence: 99%
“…The residual double bonds in these samples were hydrogenated (Scheme 2) using p-toluenesulfonyl hydrazide (TSH) in the presence of tri-n-propylamine (TPA). 48 ATR-FTIR (Figure 4a) unambiguously showed that the carboxylic acid peak (around 1710 cm −1 ) continued to increase linearly with the hydrocarboxylation reaction time (Figure 4b) allowing ready control of hydrocarboxylation levels. The carboxylic acid content of the polymers was quantified by 13 C NMR spectroscopy using cross-polarization by multiple contact period (multi-CP) technique and are presented in Table 2; these data confirmed a time-dependent increase in the carboxylic acid content.…”
Section: Pd-catalyzed Hydrocarboxylationmentioning
confidence: 97%
“…The height ratio of 0.471 for 100 • C-dried XSBR latex was enhanced by nearly 4.5 times to 2.1 after being autoclaved at 175 • C; correspondingly, both values of ∆A 966 cm−1 of PB trans-1,4 and ∆A 908 cm−1 of PB 1,2 vinyl decreased by 0.03 and 0.017, respectively, from 0.125 and 0.034 of the pre-autoclaved one. Figure 2 depicts two-step hydrothermal degradation and oxidation pathways of PB transand cis-1,4, and 1,2 vinyl units [28][29][30].…”
Section: Hydrothermal Stability Of Xsbrmentioning
confidence: 99%
“…As an important organic precursor, 1,3-butadiene is widely used in the production of polybutadiene and other copolymers, such as cis -polybutadiene rubber [ 1 , 2 ], neoprene, and styrene-butadiene polymers [ 3 – 5 ]. Owing to conjugation effects [ 6 ], 1,3-butadiene is prone to polymerize to form polymers and polyperoxides upon contact with light, heat, and oxygen in air [ 7 ], resulting in reduced performance and limiting its applications.…”
Section: Introductionmentioning
confidence: 99%